Revision der von Johann Christian Fabricius beschriebenen Ichneumonidae (Hymenoptera). - Horstmann, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 2001)
Fabricius described or named 341 species group taxa in the genera Ichneumon Linnaeus, Cryptus Fabricius, Bassus Fabricius, Pimpla Fabricius, Joppa Fabricius, Banchus Fabricius and Ophion Fabricius. All taxa belonging to the family Ichneumonidae (s. str.) are checked, 159 taxa of Ichneumonidae from the Western Palearctic Region are revised, lectotypes are designated for 79 species, and 49 new synonymies of species names are indicated. Peltastes Illiger is a senior synomyn of Tylopius Townes & Townes. A new name, Lissosculpta albopicta nom. n., is given for the junior homonym Ichneumon albatorius Fabricius. Neotypes are designated for I. dictator Geoffroy, I. frontalis Geoffroy and I. oblongus Schrank. I. visitator Poda is tentatively transferred to Gasteruption Latreille (Gasteruptiidae). Nomenclatural Actssegmentarius (Fabricius, 1787) (Alexeter), Lectotype described as Ichneumon segmentariusextenuator (Fabricius, 1804) (Anomalon), Lectotype described as Ophion extenuatorcinctorius (Fabricius, 1775) (Apsilops), Lectotype described as Ichneumon cinctoriusaggressor (Fabricius, 1804) (Astiphromma), Lectotype described as Ophion aggressoranator (Fabricius, 1793) (Barichneumon), Lectotype; nom. protectum described as Ichneumon anator; I. biscutatus Gmelin, 1790 is a nom. oblitumconfiscator Fabricius, 1804 (Bassus), Lectotype; syn. n. of Meringopus attentorius (Panzer, 1804)electorius Fabricius, 1804 (Bassus), Lectotype; nom. oblitum; syn. n. of Nematopodius formosus Gravenhorst, 1829: nom. protectummarginator Fabricius, 1804 (Bassus), Lectotype; syn. n. of Lissonota histrio (Fabricius, 1798)heterocerus Förster, 1868 (Campoplex), syn. n. of Dusona flagellator (Fabricius, 1793)arrogator (Fabricius, 1781) (Catadelphus), Lectotype described as Ichneumon arrogatormotatorius (Fabricius, 1775) (Chasmias), Lectotype described as Ichneumon motatoriusincitator (Fabricius, 1793) (Clistopyga), Lectotype described as Ichneumon incitatorcollaris Tschek, 1872 (Cryptus), syn. n. of Ischnus migrator (Fabricius, 1775)constrictor Fabricius, 1804 (Cryptus), Lectotype now a synonym of Ischnus agitator (Olivier, 1792)examinator Fabricius, 1804 (Cryptus), Lectotype now a synonym of Pimpla turionella turionella (Linnaeus, 1758)hannibal Schmiedeknecht, 1900 (Cryptus), syn. n. of Meringopus melanator (Thunberg, 1824)minutorius Fabricius, 1804 (Cryptus), Lectotype now a synonym of Ischnus agitator (Olivier, 1792)castigator (Fabricius, 1793) (Ctenichneumon), Lectotype described as Ichneumon castigatornarratorius (Fabricius, 1804) (Digonocryptus), Lectotype described as Cryptus narratoriuscurvatorius (Fabricius, 1804) (Diradops), Lectotype described as Bassus curvagtoriusregenerator (Fabricius, 1804) (Dirophanes), Lectotype described as Cryptus regeneratorflagellator (Fabricius, 1793) (Dusona), Lectotype described as Ichneumon flagellatornidulator (Fabricius, 1804) (Dusonia), Lectotype described as Ophion nidulatornotulatoria (Fabricius, 1804) (Echthromorpha agrestoria), Lectotype described as Cryptus notulatoriusdimidiator (Fabricius, 1804) (Enicospilus), Lectotype described as Ophion dimidiatorglaucatoria (Fabricius, 1793) (Eutanyacra glaucatoria), nom. protectum described as Ichneumon glaucatorius; Ichneumon albiventris Gmelin, 1790 is a nom. oblitumfornicator (Fabricius, 1781) (Exetastes fornicator), Lectotype described as Ichneumon fornicatorflavifrons (Fabricius, 1798) (Hadrodactylus), Lectotype described as Ichneumon flavifronstruncator (Fabricius, 1798) (Heterischnus), Lectotype described as Ichneumon truncatorambulatorius Fabricius, 1775 (Ichneumon), Lectotypearticulatus Geoffroy, 1785 (Ichneumon), syn. n. of Xorides praecatorius (Fabricius, 1793)atrator Fabricius, 1787 (Ichneumon), syn. n. of Meringopus melanator (Thunberg, 1824); praeocc. by I. atrator Forster, 1771bidens Fabricius, 1798 (Ichneumon), Lectotype; nom. oblitum; syn. n. of Mesoleptus cingulatus (Gravenhorst, 1829): nom. protectumbidentorius Fabricius, 1775 (Ichneumon), Lectotype now a synonym of Amblyteles armatorius (Forster, 1771)biscutatus Gmelin, 1790 (Ichneumon), nom. oblitum Barichneumon anator (Fabricius, 1793) is nom. protectum, not a synonymclavator Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Exetastes atrator (Forster, 1771); praeocc. by I. clavator Müller, 1776coerulator Fabricius, 1804 (Ichneumon), Lectotype nom. praeocc. by coerulator Weber, 1795; now a synonym of Trogus lapidator panzeri Carlson, 1975compensator Fabricius, 1793 (Ichneumon), Lectotype, syn. n. of Exatastes laevigator (Villers, 1789)cunctator Fabricius, 1793 (Ichneumon), Lectotype; syn. n. nom. praeocc. by cunctator Scopoli, 1763; now a synonym of Cryptus armator Fabricius, 1804custodiator Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Ichneumon cessator Müller, 1776destructorius Fabricius, 1793 (Ichneumon), Lectotype; syn. n. of Ischnus agitator (Olivier, 1792)dictator Geoffroy, 1762 (Ichneumon), Neotypeerectorius Fabricius, 1798 (Ichneumon), Lectotype now a synonym of Ctenichneumon edictorius (Linnaeus, 1758)exspectorius Fabricius, 1794 (Ichneumon), Lectotype; nom. oblitum; syn. n. of Ctenichneumon repentinus (Gravenhorst, 1820): nom. protectumfabricator Fabricius, 1793 (Ichneumon), syn. n. of Cratichneumon culex (Müller, 1776)fabricii Schrank, 1802 (Ichneumon), syn. n. of Spilothyrateles nuptatorius (Fabricius, 1793)falsatorius Olivier, 1792 (Ichneumon), syn. n. of Xorides praecatorius (Fabricius, 1793)fasciatus Geoffroy, 1785 (Ichneumon), syn. n. of Metopius dentatus (Fabricius, 1779)ferruginosus Gmelin, 1790 (Ichneumon), nom. oblitum; syn. n. of Patrocloides sputator (Fabricius, 1793): nom. protectumflavatorius Fabricius, 1794 (Ichneumon), Lectotype now a synonym of Lymantrichneumon disparis (Poda, 1761)flavicans Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Theronia atalantae atalantae (Poda, 1761)frontalis Geoffroy, 1785 (Ichneumon), Neotypefrontatorius Fabricius, 1793 (Ichneumon), Lectotype; nom. oblitum; syn. n. of Cratichneumon rufifrons (Gravenhorst, 1829): nom. protectumgrossorius Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Ichneumon primatorius primatorius Forster, 1771helleri Holmgren, 1878 (Ichneumon), syn. n. of Syspasis carinator (Fabricius, 1798)instigator Rossi, 1790 (Ichneumon), syn. n.; nom. oblitum of Exeristes roborator (Fabricius, 1793): nom. protectuminterruptorius Fabricius, 1804 (Ichneumon), Lectotype now a synonym of Diphyus monitorius (Panzer, 1801)intratorius Fabricius, 1793 (Ichneumon), syn. n. of Diphyus quadripunctorius (Müller, 1776)laboratorius Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Diphyus amatorius (Müller, 1776)lapidator Fabricius, 1793 (Ichneumon), Lectotype; nom. praeocc. now a synonym of Neotypus coreensis Uchida, 1930; praeocc. by I. lapidator Fabricius, 1787leucostoma Gmelin, 1790 (Ichneumon), syn. n. of Cratichneumon culex (Müller, 1776)lunulatus Villers, 1789 (Ichneumon), syn. n. of Metopius dentatus (Fabricius, 1779)mandator Fabricius, 1787 (Ichneumon), Lectotype now a synonym of Colpotrochia cincta (Scopoli, 1763)mediatorius Fabricius, 1804 (Ichneumon), Lectotype now a synonym of Obtusodonta equitatoria (Panzer, 1786)moratorius Fabricius, 1804 (Ichneumon), Lectotype; syn. n. of Melanichneumon designatorius (Linnaeus, 1758)narrator Fabricius, 1804 (Ichneumon), Lectotype now a synonym of Coelichneumon comitator (Linnaeus, 1758)natatorius Fabricius, 1798 (Ichneumon), Lectotype now a synonym of Diphyus quadripunctorius (Müller, 1776)negatorius Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Diphyus ochromelas (Gmelin, 1790)nigrator Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Coelichneumon comitator (Linnaeus, 1758)nugatorius Fabricius, 1794 (Ichneumon), Lectotype; syn. n. of Diphyus mercatorius mercatorius (Fabricius, 1793)oblongus Schrank, 1802 (Ichneumon), Neotypeobsoletorius Fabricius, 1793 (Ichneumon), Lectotype; nom. oblitum; syn. n. of Ctenichneumon divisorius (Gravenhorst, 1820): nom. protectumolitorius Fabricius, 1793 (Ichneumon), Lectotype; nom. oblitum; syn. n. of Hoplocryptus fugitivus (Gravenhorst, 1829): nom. protectumosculatorius Fabricius, 1787 (Ichneumon), Lectotype now a synonym of Exatastes atrator (Forster, 1771)pedatorius Fabricius, 1793 (Ichneumon), Lectotype; syn. n. of Diphyus quadripunctorius (Müller, 1776)pennator Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Gregopimpla inquisitor (Scopoli, 1763)quadricolor Gmelin, 1790 (Ichneumon), syn. n. of Cratichneumon culex (Müller, 1776)restaurator Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Coelichneumon serenus (Gravenhorst, 1820); praeocc. by restaurator Fabricius, 1775rusticator Thunberg, 1824 (Ichneumon), syn. n. of Lissonota accusator (Fabricius, 1793)sectator Thunberg, 1824 (Ichneumon), syn. n. of Alexeter segmentarius (Fabricius, 1787)seductorius Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Acroricnus seductor (Scopoli, 1786)semiannulator Olivier, 1792 (Ichneumon), nom. oblitum; syn. n. of Patrocloides sputator (Fabricius, 1793): nom. protectumsemiannulatus Schrank, 1776 (Ichneumon), nom. oblitum; syn. n. of Patrocloides sputator (Fabricius, 1793): nom. protectumtricolor Fabricius, 1793 (Ichneumon), Lectotype; syn. n. of Mesoleptidea prosoleuca (Gravenhorst, 1820); praeocc. by I. tricolor Schrank, 1776varius Fabricius, 1793 (Ichneumon), Lectotype now a synonym of Theronia atalantae atalantae (Poda, 1761)versicolor Gmelin, 1790 (Ichneumon), syn. n. of Cratichneumon culex (Müller, 1776)visitator Scopoli, 1763 (Ichneumon), syn. n. of Gregopimpla inquisitor (Scopoli, 1763)thoracicus Gravenhorst, 1829 (Ischnus), syn. n. of Heterischnus truncator (Fabricius, 1798)stercorator Fabricius, 1793 (Iseropus stercorator), Lectotype described as ichneumon stercoratoraccusator (Fabricius, 1793) (Lissonota), Lectotype described as Ichneumon accusatorelector Gravenhorst, 1829 (Lissonota), syn. n. of Lissonota oculatoria (Fabricius, 1798)oculatoria (Fabricius, 1798) (Lissonota), Lectotype described as Ichneumon oculatoriusalbopicta Horstmann, 2001 (Lissosculpta), nom. n. pro Ichneumon albatorius Fabricius, 1793, nec Müller, 1776firmator (Fabricius, 1798) (Listrognathus), Lectotype described as Ichneumon firmatormarginellus Holmgren, 1860 (Mesochorus), syn. n. of Astiphromma aggressor (Fabricius, 1804)ligator Gravenhorst, 1829 (Mesostenus), syn. n. of Listrognathus firmator (Fabricius, 1798)connexorius Wesmael, 1849 (Metopius), syn. n. of Metopius necatorius (Fabricius, 1793)necatorius (Fabricius, 1793) (Metopius), Lectotype described as Ichneumon necatoriusfoliator Fabricius, 1798 (Ophion), Lectotype now a synonym of Anomalon cruentatum (Geoffroy, 1785)spinator Fabricius, 1804 (Ophion), Lectotype name invalid; now a synonym of Pristomerus pacificus Cresson, 1879sputator (Fabricius, 1793) (Patrocloides), nom. protectum described as Ichneumon sputatorrusticator Wesmael, 1845 (Phaeogenes), syn. n. of Dirophanes regenerator (Fabricius, 1804)mediator Fabricius, 1804 (Pimpla), Lectotype now a synonym of Perithous scurra (Panzer, 1804)spinatorius (Fabricius, 1804) (Polycyrtus), Lectotype described as Cryptus spinatoriusapproximator (Fabricius, 1793) (Rhyssella), Lectotype described as Ichneumon approximatoranthracina Scopoli, 1763 (Sphex), nom. oblitum; syn. n. of Trogus lapidator lapidator (Fabricius, 1787): nom. protectumoccisorius (Fabricius, 1793) (Spilichneumon), Lectotype described as Ichneumon occisoriusnuptatorius (Fabricius, 1793) (Spilothyrateles), Lectotypecarinator (Fabricius, 1798) (Syspasis), Lectotype described as Ichneumon carinatorlineata (Fabricius, 1804) (Theronia), Lectotype described as Bassus lineatuslapidator (Fabricius, 1787) (Trogus lapidator), nom. protectumnotator (Fabricius, 1804) (Tromatobia), Lectotype described as Pimpla notatorauricularis Thomson, 1883 (Tryphon), syn. n. of Tryphon latrator (Fabricius, 1781)latrator (Fabricius, 1781) (Tryphon), Lectotype described as Ichneumon latratorpraecatorius (Fabricius, 1793) (Xorides), Lectotype described as Ichneumon praecatorius